THE INFLUENCE OF ORGANIZATIONAL JUSTICE ON THE COUNTERPRODUCTIVE WORK BEHAVIOR OF STATE CIVIL APPARATUS CASE STUDY: CENTER FOR SEED AND PLANTATION PLANT PROTECTION - Diwan Hadi Prakoso; Harmein Nasution; Iskandarini (RADJA PUBLIKA, 2023)
The background to this research is counterproductive work behavior found at BBPPTP Medan and indications of organizational injustice. This research discusses the influence of organizational justice which includes distributive, procedural and interactional justice on counterproductive work behavior. Quantitative methods are used in this research to test and analyze the influence of distributive justice, procedural justice and interactional justice on counterproductive work behavior. Responses from respondents were collected through distributing questionnaires using a random sampling method and using a sample of 40 respondents. Hypothesis testing uses multiple linear analysis techniques with the help of SPSS 22 software. The research results show that distributive justice has a negative and significant effect with a significance level (0.00 greater than 0.05), procedural justice has no significant effect on counterproductive work behavior with a significance level (0.272 greater than 0.05) and interactional justice has a positive and significant effect on counterproductive work behavior with a significance level of (0.005 less than 0.05). This shows that the higher the level of distributive justice received by employees, the level of counterproductive work behavior will decrease, the higher the interactional justice, the more counterproductive work behavior will increase. This research provides important implications for agencies to minimize counterproductive work behavior by paying attention to organizational justice, especially distributive justice and implementing procedural justice according to applicable regulations.